Faktor-Faktor Yang Berhubungan Dengan Kejadian Demam Berdarah Dengue (DBD) Di Desa Panji Kecamatan Sukasada Kabupaten Buleleng - I Gede Wahyu Kurniasa; I Wayan Suarta Asmara (Jurnal Kesehatan Lingkungan (JKL), 2021)
Abstract : The number of dengue cases in Buleleng Regency has increased in 2019 from IR 19,6 to 249,5 per 100.000 population. In the last 5 years, Puskesmas Sukasada I has always been in the top 3 position. The village of Panji experienced an increase in dengue cases from 0 to 50 cases in 2019. The purpose of this study was to determine the factors related to the incidence of dengue in Panji Village, Sukasada District, Buleleng Regency. The study design using the case control approach was carried out in May 2020. Data used from the results of interviews and observations. From the results of statistical tests with Chi Square from 88 respondents it can be concluded about factors that are significantly related to the incidence of DHF including the presence of Aedes aegypti mosquito larvae, the habit of using anti-mosquito repellent, eradication of mosquito nests with 3M plus and the habit of hanging clothes with a value of p 0,05. Respondents' knowledge about DHF is not significantly related to the incidence of DHF. Community participation and cross-sectoral cooperation are needed in the implementation of the DHF PSN to create a larva free village as a way to prevent the transmission of DHF.